Stability Impact Analysis of Main Construction of High-Slope PBA Concealed Excavation Metro Station - Tieyin Zhang; Lei Qiang; Xinyu Qian; Guanhua Cui; Peilong Yuan; Qiang Wang; Kunlong Zheng (Advances in Civil Engineering)
To address the issues of significant deformation and insufficient stability during the construction of a high-slope metro station, a study was conducted using indoor tests, numerical simulations, and on-site monitoring, based on a metro station in Xi’an City. Finite element analysis software was used to create a detailed model simulating the excavation of a metro station using the pile-beam-arch (PBA) method. The model analyzed the deformation patterns of the slope, shaft, and main structure, as well as the impact on surrounding buildings. The results indicate that the PBA method effectively controls excessive structural deformation. The overall deformation curve during shaft excavation is “inner-convex,” with maximum displacement concentrated at the top of the enclosure structure. Slope enclosure piles and the shaft pit enclosure structure inhibit slope displacement. On-site monitoring verifies the accuracy of the numerical simulation. These findings can serve as a reference for similar projects.